In situ formation of high-entropy carbide phase in porous SiBCN ceramic for enhanced high-temperature stability - Zifeng Hu; Huijie Wang; Dong Su (Journal of Advanced Ceramics)
Porous SiBCN ceramics exhibit great potential in high-tech structural and functional applications. However, nucleation-crystallization and carbothermal decomposition limit their use in high-temperature environments. Herein, high-entropy carbide (HEC) (Ti0.25Zr0.25Hf0.25Ta0.25)C-modified porous SiBCN ceramics (HEC/SiBCN) were successfully fabricated from a multi-metal (Ti,Zr,Hf,Ta) precursor containing polyborosilazane via solvothermal methods, freeze-drying, and pyrolysis. The porous HEC/SiBCN ceramic possesses tailorable porosity (63.5%–79.1%), low thermal conductivity (0.054–0.089 W/(m·K)), and good mechanical strength. The HEC phase is in situ formed by carbothermal reduction and solid solution reaction of the multicomponent precursor with highly active free carbon in the SiBCN matrix during the pyrolysis, which endows the porous HEC/SiBCN ceramics with outstanding thermal stability up to 1800 °C. The in situ formation of the HEC phase provides novel insight and a promising strategy for enhancing the overall performance of porous SiBCN ceramics, expanding their application in high-temperature environments.